2021
DOI: 10.1021/acssuschemeng.1c01422
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Sugars to Sugar Alcohols in the Presence of a Recyclable Ru/Al2O3 Catalyst Commercially Available

Abstract: Nowadays, the catalytic conversion of lignocellulosic biomass is the topic of many investigations.Interesting compounds that can be produced from the carbohydrate part of lignocellulose are sugar alcohols. Hence, these products production is of prime interest due to their wide use in chemical 2 industries. They can be synthesized by the hydrogenation of sugar monomers in the presence of heterogeneous catalysts that are not always stable in water. Herein, we show that a commercial Ru/Al2O3 catalyst can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…It is noted that the highest yield was obtained within a narrow temperature window (100-120 °C), and beyond that, the yield was decreased due to the possible side reactions (hydrogenolysis, dehydration and humin formations) of sugar alcohols, which was also observed by other researchers. 72,73 Apart from a batch reaction, a temperature effect is also noticed for the hydrogenation of sugars to sugar alcohols in the continuous flow reactor, with the Ru-carbon foam as a catalyst at 120 °C. 74 Hence, 120 °C is optimized with our catalysts for executing high xylitol (96%) and sorbitol (89%) selectivity.…”
Section: Catalytic Activity Testmentioning
confidence: 99%
“…It is noted that the highest yield was obtained within a narrow temperature window (100-120 °C), and beyond that, the yield was decreased due to the possible side reactions (hydrogenolysis, dehydration and humin formations) of sugar alcohols, which was also observed by other researchers. 72,73 Apart from a batch reaction, a temperature effect is also noticed for the hydrogenation of sugars to sugar alcohols in the continuous flow reactor, with the Ru-carbon foam as a catalyst at 120 °C. 74 Hence, 120 °C is optimized with our catalysts for executing high xylitol (96%) and sorbitol (89%) selectivity.…”
Section: Catalytic Activity Testmentioning
confidence: 99%
“…[22] With Ru/Al2O3 catalyst, at full conversion, higher yields in polyols where obtained from xylose and fructose than for mannose and galactose. [23] Simultaneous hydrogenation of galactose and arabinose was studied by Sifontes Herrera et al [24] and Müller et al [25] Both teams observed that arabinose hydrogenation was faster than galactose hydrogenation and estimated activation energies similar for arabinose and galactose; the former team assumed a negligible adsorption of galactose on Ru, whereas the latter team assumed a negligible adsorption of arabinose on Ru. Simultaneous hydrogenation of xylose, glucose and arabinose over Ru catalysts indicated a slightly slower rate of hydrogenation for glucose but this difference was sometimes negligible depending on the catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel-based catalysts like Raney nickel promoted or not with transition metals (Cr, Fe, Sn, Mo) have been used for the hydrogenation of sugars. However, Raney-Ni catalysts frequently undergo deactivation mainly due to leaching of Ni and poisoning of the active surface of the catalyst by the presence of organic species . As an alternative to Ni-based catalysts, noble metals (mainly Pt or Ru) have been investigated as active phases for hydrogenation of sugars to sugar alcohols. , Ruthenium was the most efficient in the selective hydrogenation of carbonyl to the corresponding alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most studied catalytic supports are carbon-based materials, oxide supports (Al 2 O 3 , TiO 2 , ZrO 2 , CeO 2 ), and silica materials (SiO 2 , SBA-15), as well as structured supports like zeolites and mesoporous ordered silica such as MCM41 or MCM48. 15 In previous works of the group, Ru catalysts supported on MCM48, AC, and TiO 2 18 were tested in the hydrogenation reaction of monomeric glucose, obtaining similar activities and 100% selectivity toward sorbitol in the temperature range between 353 and 393 K. It is important to pay attention to the stability of the catalysts to maintain activity after several cycles of reaction. For example, SiO 2 -based materials show low stability under hydrothermal conditions, leading to metal sintering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation